Creep and Recovery Behavior of Vitrimers with Fast Bond Exchange Rate. Issue 1 (5th August 2022) - Perego, Alessandro; Khabaz, Fardin
Abstract: Vitrimers encompass the desirable mechanical properties of thermosets with the recyclability of thermoplastics. This ability arises from the rearrangement of the vitrimer covalent network upon heating via a bond shuffling mechanism while its cross‐link density remains preserved. This unique feature makes vitrimers interesting candidates for the design of materials that combine dimensional stability at high temperatures and solvent resistance with the ability to be reshaped and processed. Despite these advantages, vitrimer exhibits significant creep at operating conditions where thermosets show little or no creep. As the mechanical properties of vitrimers not only depend on their chemical composition but also on the dynamics of the polymer chains, molecular dynamics (MD) simulations can provide detailed molecular mechanisms of the system of interest under macroscopic stress‐induced deformations. In this regard, the recently developed MD/Monte Carlo simulation methodology capable of capturing the bond exchange mechanics in vitrimers is used to study the creep and recovery response of a coarse‐grained model thermoset and vitrimer with a fast bond exchange rate. The time‐stress superposition principle is then successfully applied to the creep response. The resulting universal curves enable us to predict the long‐time creep behavior of both systems extending the timescale from 4 to over 10 orders of magnitude. Abstract : Vitrimers with a fast bond exchange rate show increased creep compliance by increasing applied stress or temperature.